2007
DOI: 10.1007/s00467-006-0322-0
|View full text |Cite
|
Sign up to set email alerts
|

Validation of child serum creatinine-based prediction equations for glomerular filtration rate

Abstract: Equations for estimating glomerular filtration rate (GFR) are vital in caring for patients with renal disease and the current standard, the Schwartz formula, lacks precision. We evaluated several child serum creatinine-based GFR prediction equations. Subjects aged 2-21 years who underwent iothalamate GFR (IoGFR) testing between 1999 and 2004 were studied retrospectively. GFR was estimated using: (1) Schwartz formula (SchwartzGFR), using a local k value; (2) Schwartz model (SchwartzMod) using regression-derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 29 publications
1
41
0
Order By: Relevance
“…We found that the addition of gender and height (alone) significantly improved the eGFR. This model III, 30 and 10%, respectively, of the measured iGFR. To assess the goodness of fit of the lognormal model [i.e., log(iGFR) as a Gaussian variate], we allowed model III to have residual error distributed as a generalized gamma variate and found that the shape parameter was ÏȘ0.0098 (95% confidence interval ÏȘ0.23 to 0.21), consistent with the lognormal model being appropriate to describe the distribution of iGFR as it corresponds to the case of the shape parameter being equal to 0.…”
Section: Clinical Epidemiology Wwwjasnorgmentioning
confidence: 98%
“…We found that the addition of gender and height (alone) significantly improved the eGFR. This model III, 30 and 10%, respectively, of the measured iGFR. To assess the goodness of fit of the lognormal model [i.e., log(iGFR) as a Gaussian variate], we allowed model III to have residual error distributed as a generalized gamma variate and found that the shape parameter was ÏȘ0.0098 (95% confidence interval ÏȘ0.23 to 0.21), consistent with the lognormal model being appropriate to describe the distribution of iGFR as it corresponds to the case of the shape parameter being equal to 0.…”
Section: Clinical Epidemiology Wwwjasnorgmentioning
confidence: 98%
“…To assess glomerular function, we measured serum creatinine using an enzymatic, isotopic dilution mass spectrometry-traceable method (Roche P800, Roche Diagnostics, Almere, the Netherlands) and estimated the GFR using the Schwartz formula as adapted by Zappitelli for survivors up to 18 years of age (0.469 3 [height in cm/ serum creatinine in mg/dl]) (16). The Chronic Kidney Disease Epidemiology Collaboration formula was used for all adult survivors (17).…”
Section: Definition Of Renal Dysfunctionmentioning
confidence: 99%
“…Our rationale for evaluating the use of an estimated baseline eCCl of 120 ml/min per 1.73 m 2 is that the Schwartz eCCl overestimates true GFR by as much as 25% to 30% (16), and the presence of undetected chronic kidney disease in children is extremely rare; thus, an eCCl of 100 ml/min per 1.73 m 2 could substantially underestimate baseline renal function, resulting in an underestimate of AKI during admission. We then back-calculated the estimated SCr using the Schwartz formula (eCCl 100 and eCCl 120 ), as suggested by the original authors of the RIFLE criteria (17).…”
Section: Effect Of Different Estimates Of Baseline Kidney Function Inmentioning
confidence: 99%